Kartu Domino Trigonometri: Meningkatkan Hasil Belajar Menggunakan Media Edukatif - Nalurita, Liya (Jurnal Pendidikan Matematika RAFA, 2021)
This study aims to improve student learning outcomes through the educational media of domino games in the Trigonometry Equation material in class XI-11 IPA SMA 17 Palembang. This research is a classroom action research involving repetitive self-reflection, namely planning, acting, observing, reflecting, and re-planning in two cycles. Data collection techniques used are observation and tests, data obtained by researchers of quantitative and qualitative analysis .The results obtained in this study can be seen in my cycle there are 2% of students not active in learning and from the test results there are 49% of students get good enough grades. While in cycle II there has been an increase of 0% of students who are not active in learning, and from the test results there are 74% of students getting good enough grades. Based on the results of research that has been done can conclude the use of trigonometric dominoes in educational games can improve learning creativity and learning outcomes of students of class XI-11 Mathematics and Natural Sciences 17 State High School Palembang.Abstract english version, written using Time New Roman-12, italic, justify, single space among rows.